2021
DOI: 10.1080/22221751.2021.1932607
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces cell attachment of SARS-CoV-2 spike protein by modulating the expression of ACE2, neuropilin-1, syndecan-1 and cellular heparan sulfate

Abstract: A main clinical parameter of COVID-19 pathophysiology is hypoxia. Here we show that hypoxia decreases the attachment of the receptor binding domain (RBD) and the S1 subunit (S1) of the spike protein of SARS-CoV-2 to epithelial cells. In Vero E6 cells, hypoxia reduces the protein levels of ACE2 and neuropilin-1 (NRP1), which might in part explain the observed reduction of the infection rate. In addition, hypoxia inhibits the binding of the spike to NCI-H460 human lung epithelial cells by decreasing the cell sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Our latest SARS-CoV-2 study showed that SDCs, especially SDC4 enriched in the lung, facilitate SARS-CoV-2’s entry into the cells by attaching the S1 subunit of the spike protein [ 25 ]. Other research groups also implied the role of SDC1 in SARS-CoV-2 infection [ 24 , 36 , 37 , 38 ]. Thus, SDC1 and SDC4 transfectants, created in human myeloid K562 cells, were incubated with WT and Delta spike proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Our latest SARS-CoV-2 study showed that SDCs, especially SDC4 enriched in the lung, facilitate SARS-CoV-2’s entry into the cells by attaching the S1 subunit of the spike protein [ 25 ]. Other research groups also implied the role of SDC1 in SARS-CoV-2 infection [ 24 , 36 , 37 , 38 ]. Thus, SDC1 and SDC4 transfectants, created in human myeloid K562 cells, were incubated with WT and Delta spike proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the role of syndecans in viral infections, Hudaḱ et al explored the possible interactions between SARS-CoV-2 S protein and the isoforms of syndecans, identifying that syndecan-3 and -4 facilitated the uptake of SARS-CoV-2 (Figure 1), and syndecan-4 specifically interacts with the S1 subunit of the S protein to mediate SARS-CoV-2 internalization (15). Moreover, syndecan-1 mediates cell attachment of S protein in lung epithelial cells (136). The hypoxia could modulate the expression of ACE-2 and syndecan-1 receptors, suggesting that low oxygen levels in COVID-19 patients are a defense mechanism to reduce the expression of entry receptors and attachment factors located in cholesterol-rich lipid rafts (136).…”
Section: Syndecansmentioning
confidence: 99%
“…Moreover, syndecan-1 mediates cell attachment of S protein in lung epithelial cells (136). The hypoxia could modulate the expression of ACE-2 and syndecan-1 receptors, suggesting that low oxygen levels in COVID-19 patients are a defense mechanism to reduce the expression of entry receptors and attachment factors located in cholesterol-rich lipid rafts (136). Notably, the distribution of syndecan-4 is ubiquitous, and its expression is abundant in the lungs, one of the target organs of SARS-CoV-2 (137).…”
Section: Syndecansmentioning
confidence: 99%
“…Cell culture data derived from alveolar and bronchial epithelial cells have revealed that although some of the HIF-α targets, such as VEGF, are upregulated by SARS-CoV-2, VHL that targets HIF-α to degradation is also upregulated [28]. In turn, HIF-1α activation inhibits SARS-CoV-2 infection in the these cells [22], at least in part due to lower ACE2 expression and subsequent reduction of cell attachment of the viral spike protein [29]. In serum, lower levels of EPO have been detected in COVID-19 critical and deceased patient groups than in healthy ones [30].…”
Section: Introductionmentioning
confidence: 99%